2020
DOI: 10.1136/jnnp-2020-323611
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomics yields insight into ALS disease mechanisms

Abstract: ObjectiveTo identify dysregulated metabolic pathways in amyotrophic lateral sclerosis (ALS) versus control participants through untargeted metabolomics.MethodsUntargeted metabolomics was performed on plasma from ALS participants (n=125) around 6.8 months after diagnosis and healthy controls (n=71). Individual differential metabolites in ALS cases versus controls were assessed by Wilcoxon rank-sum tests, adjusted logistic regression and partial least squares-discriminant analysis (PLS-DA), while group lasso exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 57 publications
5
76
0
7
Order By: Relevance
“…The energy and phospholipid metabolism have also been found to be impaired in patients with HD that ultimately affects the function of neurons (53,69). Glucose metabolism is dysregulated in AD patients (70) and in area of the pons and cerebellum of MSA patients (71,72), while an association of fatty acid metabolism with the development of ALS was observed (73). Finally, in our recent study we reported on the identification of metabolic biomarkers of early diagnosis and progression of FXTAS and on their association with altered lipid metabolism including free fatty acids, acylcarnitine, sphingolipids, diacylglycerol, and phospholipids, in individuals who developed the symptoms of FXTAS over time (25).…”
Section: Discussionmentioning
confidence: 99%
“…The energy and phospholipid metabolism have also been found to be impaired in patients with HD that ultimately affects the function of neurons (53,69). Glucose metabolism is dysregulated in AD patients (70) and in area of the pons and cerebellum of MSA patients (71,72), while an association of fatty acid metabolism with the development of ALS was observed (73). Finally, in our recent study we reported on the identification of metabolic biomarkers of early diagnosis and progression of FXTAS and on their association with altered lipid metabolism including free fatty acids, acylcarnitine, sphingolipids, diacylglycerol, and phospholipids, in individuals who developed the symptoms of FXTAS over time (25).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a study conducted by Nakken and colleagues showed that high early-aged levels of BMI are associated with low ALS risk several decades later [ 169 ]. Moreover, a study conducted by Goutman and colleagues showed that higher premorbid BMI is associated with slower ALS progression [ 170 ]. A high BMI at diagnosis is also associated with a better survival suggesting it as a marker of disease severity [ 170 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study conducted by Goutman and colleagues showed that higher premorbid BMI is associated with slower ALS progression [ 170 ]. A high BMI at diagnosis is also associated with a better survival suggesting it as a marker of disease severity [ 170 ].…”
Section: Discussionmentioning
confidence: 99%
“…Derived from the high-energy product creatine, blood creatinine is widely used as a biomarker of kidney function. Previous studies have demonstrated decreased creatinine levels in those with motor neuron diseases, including ALS [ 10 , 12 , 31 ], spinal muscular atrophy (SMA) [ 32 ], and spinal and bulbar muscular atrophy (SBMA) [ 31 ]. Consistent with our study, lower levels of creatinine have been observed in the plasma [ 10 , 12 , 31 ], serum [ 32 ], and CSF [ 14 ] of ALS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The profiles of metabolites are produced by catabolic and anabolic processes in different tissues, serving to reflect dysregulated cellular and metabolic processes. In ALS, the metabolic profiles revealed by various metabolomics platforms show a disturbance of a number of ALS-associated metabolic pathways, including amino acid, pyruvate, and lipid metabolism [ 7 , 8 , 9 , 10 ]. Altered levels of sphingolipids have been reported in the plasma of ALS patients [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%